Utility from battery energy storage systems in rural sub-Saharan African solar PV microgrids - Bergman, Anton (My University, 2021)
Almost 800 million people on the planet does not have access to a reliable supply of electricity. Universal access to modern sources of energy is a necessary step for poverty alleviation in many regions concentrated around the equator. Solar PV is often used because of the high solar irradiance in these areas but will imply difficulties for delivering a stable and continuous supply of electricity, some of which the addition of a battery energy storage system eventually could solve.This study was made with the intent to find how utility could be created from an additional battery energy storage for a solar PV microgrid application in a rural Sub-Saharan African context. A method was designed to translate improvements in the electrotechnical attributes of peak capacity, availability and reliability in to social, economical and environmental utility from household, productive and community use. The results showed that social utility from more energy supplied by an improved availability and reliability of electricity will see the most amount of utility, where high environmental utility by reduced emissions will follow as a result of this. Some economical utility could be seen, but requiring longer periods of time before any major differences can be distinguished. The overall utility from added battery energy storage was concluded to be high and the amount of utility a battery energy storage system creates is dependent on its ability to supply either additional power and energy.
Keywords: microgrids; rural; solar PV; utility; battery energy storage systems; sub-saharan africa